Tri-SUS: a yeast split-ubiquitin assay to examine protein interactions governed by a third binding partner. Issue 2 (3rd December 2020) - Zhang, Ben; Xia, Lingfeng; Zhang, Yaxian; Wang, Hui; Karnik, Rucha
Abstract : The yeast Tri-SUS system can be used to study tripartite protein–protein interactions between bait and prey protein pairs by modulation of expression of their binding partner